Cross-border approach to regions’ smart specialization: experience of the EU member states - Demedyuk, Olha; Prytula, Khrystyna (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
In the recent decade, the EU Member States have been actively implementing the regional development policy based on innovative strategies of smart specialization. However, lately, European researchers have been paying increasing attention to the issues of regions’ capacity to overcome the boundaries of administrative units inside the country and abroad and to the need to consider regions in the context of their functioning among others, especially from the viewpoint of the growing role of their innovative networks in global value chains. That is why currently the EU is addressing the development of cross-border smart specialization strategies. The paper aims to study the European experience on the functioning of cross-border innovation systems and joint strategic planning of cross-border regions’ development based on smart specialization and to outline the opportunities to implement the EU experience of cross-border approach to smart specialization in cross-border regions of Ukraine with EU Member States. The paper analyzes the views of foreign researchers on the links between innovation systems in cross-border space that constitute the theoretical basis of the study of cross-border smart specialization strategies, namely regarding the dimensions and level of their development. The research of European scientists on cross-border innovation systems in specific cross-border regions is examined, in particular on Spanish-French and German-French borders. Directions of implementation of smart specialization projects in cross-border context under the EU programs and other EU instruments that support regions in cooperation for the elaboration of joint view of development with neighbouring economically, socially, culturally, and historically close regions are outlined. The experience and methodology of the first cross-border smart specialization strategy for Spanish and Portuguese regions are studied in detail. The opportunities to use the EU experience by several Western Ukrainian regions based on the joint smart specialization priorities with the neighboring EU states are outlined. For this purpose, 1) the RIS3 strategies of the regions of Poland and Romania adjoining Ukraine and Regional Development Strategies of respective Ukrainian regions were analyzed to detect similar smart specialization priorities; 2) the clusters in the mentioned regions were analyzed as main drivers of achievement of smart specialization goals to detect similar or complementary functioning areas.